Problem gambling and gaming in elite athletes - Håkansson, A. (Addict Behav Rep, 2018)
BACKGROUND: High-level sports have been described as a risk situation for mental health problems and substance misuse. This, however, has been sparsely studied for problem gambling, and it is unknown whether problem gaming, corresponding to the tentative diagnosis of internet gaming disorder, may be overrepresented in athletes. This study aimed to study the prevalence and correlates of problem gambling and problem gaming in national team-level athletes. METHODS: A web-survey addressing national team-level athletes in university studies (survey participation 60%) was answered by 352 individuals (60% women, mean age 23.7), assessing mental health problems, including lifetime history of problem gambling (NODS-CLiP) and problem gaming (GASA). RESULTS: Lifetime prevalence of problem gambling was 7% (14% in males, 1% in females, p < 0.001), with no difference between team sports and other sports. Lifetime prevalence of problem gaming was 2% (4% in males and 1% in females, p = 0.06). Problem gambling and problem gaming were significantly associated (p = 0.01). CONCLUSIONS: Moderately elevated rates of problem gambling were demonstrated, however with large gender differences, and interestingly, with comparable prevalence in team sports and in other sports. Problem gaming did not seem more common than in the general population, but an association between problem gambling and problem gaming was demonstrated.